Analisis Frasa pada Buku Panduan Belajar dan Bermain Berbasis Buku untuk Pengajar PAUD - Dian Nugraheni; Evi Nur Mala Sari; Putri Dzakiyyatul Khotimah; Nida Rufaida; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Pusat Riset dan Inovasi Nasional, 2023)
Phrases can start with a preposition or a verb and also can just be the subject. Phrases are in a syntactic function which is formed from a combination of words. Often found in the text in a sentence, for example, is one of which is in the Book-Based Play and Learning Guide for Early Childhood Teachers. This study discusses the analysis of the use of phrases in the textbook. The aim is to find out the relevance of the sentence study of the types of phrases contained in book-based play and study guides for early childhood teachers. This study uses a qualitative method with a descriptive approach. The data collection method uses observation techniques and examines how the language is applied, and the note-taking method is also used to record the structure being analyzed. This study found that there are 3 verb phrases, 3 adjektiva phrases, 3 numeral phrases, 3 noun phrases, 3 exocentric phrases, and 3 endocentric phrases. One of the benefits of this research is that we understand more about the types of phrases in each sentence.